An empirical study on lean management and HRM practices in relation towards operational performance - Azhani, Ismail; Yuserrie, Zainuddin (Turkish Online Journal of Design, Art and Communication, 2018)
In recent years, the matter of lean management (LM) and human resource management (HRM) practices have been commonly used to observe operational performance (OP). One of the distinctive features of LM and HRM practices is that better performance is achieved through the people in the organization. Many researchers have demonstrated that investments in human capital can significantly influence organizational objectives and outcomes. The resource-based view (RBV) theory perspective has been extensively utilized to empirically test and predict these organizational objectives and outcomes. This study investigates from RBV theory perspective, the mediating effect of HRM practices on the relationship between LM and OP within public sector in Malaysia. The main research question addressed by this study is whether LM enhances OP directly or indirectly through the support of the HRM practices. A survey research method is adopted to collect data from Malaysia local authorities. The analysis of the research model uses Partial Least Square (PLS) based software SmartPLS 3. The results will provide practitioners with guidelines in implementing LM more efficiently and effectively for enhancing OP of their organizations.